Science of administrative law and its teaching at Lviv University during the Austro-Hungarian Period - Gavrylenko, O. A. (Аналітично-порівняльне правознавство, 2025)
The article provides a detailed study of the process of formation and further development of the science of administrative law at Lviv University during the period of the Austro-Hungarian monarchy. Special attention is given to the analysis of the specifics of administrative-legal science within the complex historical and legal environment of Austro-Hungary, which combined multiculturalism, legal tradition, and imperial governance. It is noted that Lviv University functioned not only as a center of higher education but also as a powerful hub of scholarly thought, playing a decisive role in the development of legal science and the training of legal professionals in Central and Eastern Europe. The author conducts a comprehensive analysis of the origins of administrative law as an independent academic discipline, revealing the features of the main courses, curricula, and textbooks used at the university. This allows tracing how a coherent and systematic structure for teaching administrative law was formed, meeting the needs of the time and the requirements of the Austro-Hungarian Empire. Particular attention in the article is paid to leading scholars of Lviv University – Johann Koppel, Tadeusz Pilat, Leon von Bilinski, Jozef Buzek, Oswald Balzer, and other prominent professors who made significant contributions to the development of this branch of law. Their scientific works, methodological approaches, and influence on not only Ukrainian but also European administrative-legal science are analyzed. The interaction of the Lviv school with major European legal traditions is also examined, which contributed to the formation of a unique scientific platform. The study outlines the role of the science of administrative law at Lviv University in a broader context – the formation of legal thought within the Austro-Hungarian monarchy, the development of Ukrainian legal science and legal culture. The influence of the Lviv scholarly school on the further development of administrative law in the interwar period is analyzed, emphasizing its importance from both historical and methodological perspectives. In the concluding part of the article, the main results of the research are summarized, and prospects for further scholarly investigations are outlined. In particular, the author stresses the need for deeper study, thorough analysis of archival materials, and comparative research of the Lviv school in the context of European legal science.